LEVERAGING THE HERITAGE SIGNIFICANCE OF THE CESME IN ISTANBUL TO CREATE A QUALITY URBAN PLACE - Nur Izzati Rosli; Mohd Iqbal Hashim (Journal of Islamic, Social, Economics and Development, 2023)
Istanbul's public fountain (cesme) has the potential to revitalise urbanneighbourhoods following its significance as an Islamic heritage. Nevertheless, more arebecoming out of favour since their decline as functional objects. Therefore, it is pertinent to seehow we can reuse them as a generator for place-making. Can the cesme be a generator ofquality urban neighbourhood revitalisation? Although much research has addressed thecesme's typology and topology, only some address the object from the Islamic city planningperspective. This article is a serious attempt to address its Islamic heritage significance and –new – meaning in the urbanity of Istanbul. The study in this article was carried out by adoptinga participatory immersion study. Firstly, the urban experience was recorded and reflected uponto assess its vitality. This is followed by a comparative analysis of the repurposed cesme foundduring the field study. As an urban object, the cesme still has a strong cultural attachment toIstanbul. By returning them to the public with a repurposed use, a new meaning is appropriatedfor the cesme. Subsequently, the public place it defined is given new vitality. This newperspective on cesme and its potentiality can add to the approach to heritage-led regeneration.By repurposing the traditional workplace into a third place, its meaning as a social productioncontinues to the current time.